Skin fragility caused by biallelic KRT10 mutations: an intriguing form of self‐improving epidermolytic ichthyosis. (26th September 2019) - Frommherz, L.; Küsel, J.; Zimmer, A.; Fischer, J.; Has, C.
Summary: Autosomal recessive epidermolytic ichthyosis is a rare skin condition associated with KRT10 loss‐of‐function mutations. It presents with severe life‐threatening clinical manifestations. Here we describe a case of autosomal recessive epidermolytic ichthyosis with an unusually mild, spontaneously improving phenotype. Erythroderma and superficial blistering were present at birth, but the skin recovered and remained almost intact at the age of 1 year. Mild scaling on the neck and skin fragility manifesting as superficial erosions after scratching were the only clinical features as the child grew. As a cause, previously unreported compound heterozygous KRT10 pathogenic variants were found: a nonsense mutation leads to mRNA decay, while the other synonymous variant induces a leaky splice site, explaining the residual keratin 10 expression and mild clinical phenotype. What's already known about this topic? Autosomal recessive epidermolytic ichthyosis is a rare skin condition caused by loss‐of‐function KRT10 mutations. The clinical phenotype is severe with superficial skin blistering, scaling and hyperkeratosis. What does this study add? Here we extend the mutational and phenotypic spectrum of autosomal recessive epidermolytic ichthyosis. Our case presented with erythroderma and superficial blistering at birth, but the skin recovered and was almost intact at the age of 1 year. The only disease manifestations were mild scaling on the neck and skin fragility appearing as superficial erosions after scratching. The causative factors were found to be one nonsense mutation in KRT10 that leads to mRNA decay, and one synonymous variant that affects the donor splice site of exon 3. We hypothesize that this leaky splice site explains the residual keratin 10 expression and self‐improving clinical phenotype.